Biophysical characterization and ligand-binding properties of the elongation factor Tu from Mycobacterium tuberculosis. (7th January 2019) - Yang, Juanjuan; Hong, Jing; Luo, Ling; Liu, Ke; Meng, Chun; Ji, Zhi-liang; Lin, Donghai
Abstract: Mycobacterium tuberculosis ( Mtb ) is the key devastating bacterial pathogen responsible for tuberculosis. Increasing emergence of multi-drug-resistant, extensively drug-resistant, and rifampicin/isoniazid-resistant strains of Mtb makes the discovery of validated drug targets an urgent priority. As a vital translational component of the protein biosynthesis system, elongation factor Tu (EF-Tu) is an important molecular switch responsible for selection and binding of the cognate aminoacyl-tRNA to the acceptor site on the ribosome. In addition, EF-Tu from Mtb ( Mtb EF-Tu) is involved in the initial step of trans -translation which is an effective system for rescuing the stalled ribosomes from non-stop translation complexes under stress conditions. Given its crucial role in protein biosynthesis, EF-Tu is identified as an excellent molecular target for drug design. Here, we reported the recombinant expression, purification, biophysical characterization, and structural modeling of the Mtb EF-Tu protein. Our results demonstrated that prokaryotic expression plasmids of pET28a- Mtb EF-Tu could be expressed efficiently in Escherichia coli . We successfully purified the 6× His-tagged proteins with a yield of 16.8 mg from 1 l of Luria Bertani medium. Dynamic light scattering experiments showed that Mtb EF-Tu existed in a monomeric form, and circular dichroism experiments indicated that Mtb EF-Tu was well structured. Moreover, isothermal titration calorimetry experiments displayed that the purified Mtb EF-Tu protein possessed intermediate binding affinities for guanosine-5′-triphosphate (GTP) and GDP. The GTP/GDP-binding sites were predicted by flexible molecular docking approach which reveals that GTP/GDP binds to Mtb EF-Tu mainly through hydrogen bonds. Our work lays the essential basis for further structural and functional studies of Mtb EF-Tu as well as Mtb EF-Tu-related novel drug developments.